Reading Practices of Students in Media Communication System of 21st Century: ‘Book Enthusiasts’ and ‘Digital Adepts’ - V. Ya. Askarova; L. B. Zubanova; N. L. Zykhovskaya (Научный диалог)
The article explores the reading practices of contemporary students in the context of the development of digital technologies. The authors interpret the results of sociological research conducted, which reveal students’ attitudes towards various reading practices in the midst of media transformations (surveys, focus groups, analysis of drabbles). The study investigates students’ attitudes towards reading (the value of reading and frequency of engagement), differentiating interests and factors influencing reading activity. The effectiveness of promoting and supporting reading in libraries, universities, the film industry, and opinion leaders is evaluated. The conclusion is drawn that there is no basis for a fundamental distinction between supporters of traditional (book enthusiasts) and digital (digital adepts) reading. Both are fully integrated into the traditional paper and digital book environment. Modern digital and visual communication technologies were found to be the most significant means of encouraging reading for both categories of respondents. The lines of digital inequality are primarily determined by the level of engagement in media communication and the ability to generate creative content. A predominantly passive position of respondents towards reading content online is observed. The conclusion is made about the gap between the declared, recognized, and implemented value of reading.